Optimization of the Reaction Conditions for the Synthesis of Dihydrobenzofuran Neolignans - Dias,Herbert J. (2021)
We have optimized the experimental conditions for the silver(I)-promoted oxidative coupling of methyl p-coumarate (I) and methyl ferulate (II), which is the most frequently used methodology to synthesize the bioactive dihydrobenzofuran neolignans 1 ((±)-trans-dehydrodicoumarate dimethyl ester) and 2 ((±)-trans-dehydrodiferulate dimethyl ester). Most of the tested conditions affected the conversion (i.e., the consumption of I and II) and the selectivity (i.e., the percentage of I and II that was converted into 1 and 2, respectively), so the optimized conditions were the ones that afforded the best balance between conversion and selectivity. Silver(I) oxide (0.5 equiv.) is the most efficient oxidant agent amongst the silver(I) reagents that were tested to convert methyl esters I and II into compounds 1 and 2, respectively. Acetonitrile, which has not yet been reported as a solvent for this reaction, provided the best balance between conversion and selectivity, besides being “greener” than other solvents that are more often employed (e.g., dichloromethane and benzene). Under the optimized conditions, the reaction time decreased from 20 to 4 h without significantly impacting the conversion and selectivity.